The use of the apparatus of growing pyramidal networks to assess the innovation potential of chemical companies at different stages of a crisis situation - T. V. Kakatunova; S. S. Shirokov; E. Y. Chicherova (Путеводитель предпринимателя)
Indicators for the evaluation of innovative and logistical capacity of organizations at different stages of the crisis offered. The possibility of using the growing pyramidal network to diagnose potential of the organization of these types proved.